2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferr 2020
DOI: 10.1109/ifcs-isaf41089.2020.9234883
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in AlScN: Switching, Imprint and sub-150 nm Films

Abstract: The discovery of ferroelectricity in AlScN allowed the first clear observation of the effect in the wurtzite crystal structure, resulting in a material with a previously unprecedented combination of very large coercive fields (2-5 MV/cm) and remnant polarizations (70-110 µC/cm²). We obtained initial insight into the switching dynamics of AlScN, which suggests a domain wall motion limited process progressing from the electrode interfaces. Further, imprint was generally observed in AlScN films and can tentativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
2
15
0
Order By: Relevance
“…In relaxed films deposited on Si, an increase of the c ‐lattice parameter with lower Sc concentration was observed. [ 17 ] In the present case, the c ‐lattice parameter changes also due to elastic deformation of the unit cell imposed by the epitaxial strain which superimposes the change of the c ‐lattice parameter due to Sc variation.…”
Section: Structural Characterizationmentioning
confidence: 82%
See 2 more Smart Citations
“…In relaxed films deposited on Si, an increase of the c ‐lattice parameter with lower Sc concentration was observed. [ 17 ] In the present case, the c ‐lattice parameter changes also due to elastic deformation of the unit cell imposed by the epitaxial strain which superimposes the change of the c ‐lattice parameter due to Sc variation.…”
Section: Structural Characterizationmentioning
confidence: 82%
“…The foremost goal of the electrical characterization of our samples was to determine if they are ferroelectric and how their ferroelectricity compares to those films deposited on the common polycrystalline metal interfaces. [ 12,17 ] Displacement current density measurements in dependence of the electric field ( J – E measurements) are at the core of ferroelectric characterization and were performed on capacitors with different Al 0.72 Sc 0.28 N film thicknesses as well as different Sc concentrations with a constant thickness of 100 nm. If not stated otherwise, the contacted pad size was 50 × 50 µm 2 and the measurement frequency 1.5 kHz.…”
Section: Electrical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxi- where P s is the spontaneous polarization, A is the capacitor size, and t FWHM is the current peak width. The switching current of a 100 µm diameter capacitor of Al 0.7 Sc 0.3 N (P s = 110 µC cm −2 [14][15][16][17][18]) reaches approximately 100 mA for a 100 ns switching time. Thus, a measurement system capable of measuring the intrinsic behavior of the sample without the circuit itself dominating the measurement requires a total design including large current and voltage capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In the PUND test, this gap was maintained and it was observed that the remanent polarizations in the positive and negative directions were not equal. Given that the top and bottom electrodes of the device are not of the same material, it can be concluded that different metal electrodes play a role in the ferroelectricity of the film [ 16 ].…”
Section: Introductionmentioning
confidence: 99%